Znaczenie turystyki żeglarskiej w rozwoju lokalnej gospodarki na przykładzie gminy Darłowo - JOLANTA ZIEZIULA; PIOTR NOWACZYK (Ekonomiczne Problemy Turystyki, 2018)
The paper aims at determining a role of sail tourism in local economic development, basing on the theory of an economic basis. According to the theory, external factors such as tourism, stimulate a local economic development. Tourists pour additional money to local economy, that supports the development. In the period 2004-2016, sailors were more and more interested in the marine port of Darłowo and the sail tourism has started to play an increasing role in the local economic development. Investments in marine infrastructure for sailing became profitable. Perspectives for the sail tourism development are promising. However, the tourism development requires extending marine facilities for sailing and widening a scope of additional services. A promotion of sailing, international cooperation and creating sail cluster may essentially support the sail tourism and the economic development of Darłowo’s gmina.